Model Pengembangan Kurikulum “Model Beauchamp, Roger dan Douglas Brown” - fauziyah, luqi; Hanifah, Umi (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2024)
This research discusses three curriculum development models, namely the Beauchamp Model, Roger Model, and Douglas Brown Model. The Beauchamp Model emphasizes a systematic and administrative approach in curriculum development, the Roger Model focuses on interpersonal interactions and direct experiences in learning, while the Douglas Brown Model prioritizes cognitive, socio-affective and linguistic principles in language teaching. This research uses a descriptive qualitative method with a literature study approach. Data was collected from various academic sources, such as books, scientific journals, and educational documents related to curriculum development. The analysis was carried out through a comparative study of the three models to identify their strengths, weaknesses and relevance in the educational context in Indonesia. The research results show that each model has its own unique approach to curriculum development. The Beauchamp Model is more suitable for a structured and centralized education system, the Roger Model is suitable for an experience-based approach and active participation of students, while the Douglas Brown Model is more effective in language learning. By understanding these various models, educational institutions can select and adapt the most relevant models according to their learning needs.